Seed morphology and histology of some Paronychia taxa (Caryophyllaceae) from Turkey - Kaplan, Ayse; Çölgeçen, Hatice; Büyükkartal, H Nurhan (Bangladesh Journal of Botany, 2010)
Seed morphology and histology of 12 taxa (nine species, two subspecies, one variety) of Paronychia Miller (Caryophyllaceae) by light and scanning electron microscopes revealed that seeds are laterally compressed, reniform, and hilums are linear. Testa surface structures are alveolate-scalariform, colliculate, reticulate-alveolate, rugose and ruminate. Differences in cuticle and papillae properties of epidermal cells have been observed. A dichotomous key has been developed for Paronychia agryloba Stapf, P. angorensis Chaudri, P. arabica (L.) DC. subsp. euphratica Chaudri, P. carica Chaudri, P. cataonica Chaudri, P. condensata Chaudri, P. davisii Chaudri, P. dudleyi Chaudri, P. galatica Chaudri, P. kurdica Boiss subsp. kurdica var. kurdica, P. kurdica Boiss subsp. montis-munzur Chaudri and P. mughlaei Chaudri. Key words: Paronychia; Caryophyllaceae; Seed morphology; Seed histology; Turkey DOI: 10.3329/bjb.v38i2.5142 Bangladesh J. Bot. 38(2): 171-176, 2009 (December)